Indirect effect of elevated CO2 concentration on Bemisia tabaci MEAM1 feeding on Bt soybean plants. (12th September 2020) - De Paulo, Paula Daiana; Pereira, Eliseu José G.; Oliveira, Eugenio E.; Fereres, Alberto; Garzo, Elisa
Abstract: The development of herbivore insects is influenced by the quality of their host plants. Elevated CO2 alters plant metabolism, which may change the nutritional quality of the plant, modifying the life history and feeding behaviour of herbivore insects. Understanding how insect pests respond to increasing CO2 concentration is essential for predicting the impact of the pest on food security. In this study, we investigated the effects of elevated CO2 (eCO2 ) on the life history and feeding behaviour of the MEAM1 species of Bemisia tabaci on a Bt soybean cultivar. We found that eCO2 increased the egg to adult development time and reduced the reproductive responses (fecundity and fertility) of B. tabaci . The whitefly B. tabaci that fed on the soybean plants grown under eCO2 conditions was negatively influenced by several traits related to the host plant resistance, such as the time spent on phloem sap ingestion. Furthermore, we evaluated the changes in the C:N concentration and plant morphology of the Bt plants. The biomass (weight of leaves and stems) of the Bt soybean plants grown under eCO2 conditions was significantly increased, and the elevated C:N ratio in the phenological stage V6 (i.e. when the plants had six trifoliate leaves developed) was the most pronounced difference in the Bt soybean plants subjected to eCO2 treatment. Taken together, our results indicate that Bt plants cultivated under eCO2 inhibit B. tabaci feeding, which can reduce whitefly infestations of the soybean fields.